Penerapan Metode Pembelajaran Efektif dalam Pendekatan Layanan Bimbingan Belajar pada Kegiatan PPL di SD Negeri Kandang Panjang 02 - Okpatrioka Okpatrioka; Ginawati Ginawati; Nono Yatno (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
Laziness is a behavior that is often experienced by almost everyone, including students. As the next generation of the nation, students should have high enthusiasm in pursuing knowledge. Education is not only limited to the classroom; knowledge can be found anywhere and anytime. Therefore, it is important for students to try to overcome their lazy habits, because laziness can have detrimental effects. For example, if a student is lazy to study, he will lose the opportunity to gain useful knowledge. On the other hand, if the student is diligent in studying and is able to overcome laziness, they will gain broader knowledge and insight. Problems that often arise are the lack of enthusiasm from students in the learning process, non-compliance in completing assignments and taking notes, and the tendency to fall asleep or leave the classroom during the lesson. To overcome this problem, the method of implementing group guidance is carried out in three stages: First, starting with the introduction and delivery of material on the theme of "Learning", which aims to introduce the concept of effective learning and foster student interest. Second, an explanation of the material regarding "Learning Motivation" to encourage students to study hard for a brighter future. Third, the presentation of material on the theme "Why do we have to go to school?" which provides students with an understanding of the importance of education and the reasons to continue learning. Through this group guidance process, it is hoped that it can foster an effective learning spirit and encourage students to participate more actively in learning activities in the classroom.